Hybrid energy storage systems for power system frequency control - Zhou, Xiangyu (2018)
In order to overcome the ever-challenging environmental issues caused by greenhouse gas emission, conventional energy sources are gradually being replaced by renewable energy sources. However, the increasing penetration of renewable energy sources leads to the decrease of power system inertia, since renewable sources barely contribute to the inertial response. To tackle this problem, a hybrid energy storage system (HESS), which is composed of the battery and the supercapacitor, is proposed in this project to enhance the system frequency control performance.